Profil Mental Toughness dan Prestasi pada Atlet Gymnastic Tingkat Daerah - Novia Laila Fitri; Helmy Firmansyah; Jajat Darajat Kusumah Negara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to describe the mental toughness profile and achievement level of regional-level gymnastics athletes. Mental toughness is regarded as a crucial psychological factor contributing to performance consistency and athletic success, particularly in gymnastics, a sport that demands movement accuracy, balance, and high concentration under subjective judging pressure. This study used a quantitative descriptive method with a total sampling technique involving 11 active regional-level gymnastics athletes. Data were collected using the Sports Mental Toughness Questionnaire (SMTQ), which measures three dimensions: confidence, constancy, and control, along with achievement data based on medals earned in official competitions. Data were analyzed descriptively using SPSS 23. The results showed that (1) the total mental toughness score was in the moderate category (mean = 39.36; SD = 3.23), with the majority of athletes (63.6%) in the moderate category, 27.3% in the low category, and only 9.1% in the high category; (2) the confidence dimension was the most prominent component (mean = 18.00), while the control dimension was the most fragile (mean = 10.00; SD = 3.16); (3) in terms of achievement, the low and high categories showed equal proportions (36.4% each); and (4) a high mental toughness score does not always correspond to higher medal achievement. These findings emphasize the importance of strengthening the control dimension through structured mental training programs for regional-level gymnastics athletes. Keywords: Gymnastics Athletes, Mental Toughness, Achievement, SMTQ